2020
DOI: 10.1177/0963662520954370
|View full text |Cite
|
Sign up to set email alerts
|

The “replication crisis” in the public eye: Germans’ awareness and perceptions of the (ir)reproducibility of scientific research

Abstract: Several meta-analytical attempts to reproduce results of empirical research have failed in recent years, prompting scholars and news media to diagnose a “replication crisis” and voice concerns about science losing public credibility. Others, in contrast, hoped replication efforts could improve public confidence in science. Yet nationally representative evidence backing these concerns or hopes is scarce. We provide such evidence, conducting a secondary analysis of the German “Science Barometer” (“Wissenschaftsb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…Populist political orientation : (AfD supporters, yes/no).The Science Barometer asks respondents for their preferences among the political parties in Germany. We coded AfD (the populist right-wing party “Alternative for Germany”) versus non-AfD supporters as a binary indication of populist attitudes [ 42 ]. Generally, populist ideas do not only criticize a political establishment, but they may also challenge academic elites, suggesting that scientific knowledge (e.g., about COVID-19) is useless, ideologically biased, and inferior to ordinary people’s common sense [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Populist political orientation : (AfD supporters, yes/no).The Science Barometer asks respondents for their preferences among the political parties in Germany. We coded AfD (the populist right-wing party “Alternative for Germany”) versus non-AfD supporters as a binary indication of populist attitudes [ 42 ]. Generally, populist ideas do not only criticize a political establishment, but they may also challenge academic elites, suggesting that scientific knowledge (e.g., about COVID-19) is useless, ideologically biased, and inferior to ordinary people’s common sense [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…21) significantly exceeding that reported in the overall sample. In regard to the often cited replication crisis in Psychology [15] and other fields [16][17][18], it is crucial to evaluate if these effect sizes can withhold further inspection. Moreover, replicating these studies can help to address their shortcomings and add to the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can see a clear link between political ideology and public trust in science in the United States and the United Kingdom in recent years. Moreover, the link between conservative political ideology and distrust of science has also been pointed out in a study conducted in Germany (Mede, Schäfer, Ziegler, & Weißkopf, 2020). However, since the influence of political ideology on the attitude toward science in Japan was not evaluated in the survey conducted by the Pew Research Center (2020) and no other similar studies were found, the relationship between the two remains unclear.…”
Section: Literature Reviewmentioning
confidence: 94%